Agro-technology for climate-smart agriculture and resilience to climate extremes in sub-Saharan Africa - Arenas Calle, Laura N.; Jennings, Stewart; Challinor, Andrew J. (IOP Publishing, 2024)
Agro-technologies such as irrigation and new crop varieties can reduce climate risk for agricultural production in sub-Sahara Africa (SSA). SSA has the highest maize yield gaps globally, despite its importance as a staple crop in the region. Reducing maize yield gaps is key to tackling food insecurity; however, closing yield gaps might imply an increased greenhouse gas (GHG) emission cost. Climate smart agriculture (CSA) seeks to minimise this cost whilst maximising productivity and resilience. One key element of CSA is resilience to extreme events, although this is rarely examined. Accordingly, we assess the climate smartness of contrasting agro-technology and climate scenarios to assess both resilience to extremes and the overall climate smartness of the scenarios. We use simulations from an existing integrated modelling framework for Malawi, Tanzania, and Zambia, centred on 2050. Four scenarios were examined, defined by combinations of high vs. low agro-technology adoption and high vs. low climate risk (RCP2.6 and RCP8.5). We calculated a climate smartness index (CSI) to the model outputs that quantify the trade-offs between greenhouse gas emissions and agricultural productivity. CSI scores showed that the increase in GHG emissions from improved agro-technology is compensated for the yield benefits. Agro-technology in SSA can therefore benefit the pillars of climate-smart agriculture, namely increased mitigation, adaptation, and productivity. Further, we show that improved maize varieties and irrigation can substantially reduce future yield shocks and enhance resilience to climate change extremes in SSA, pointing to best-bets for agro-technology adoption. Irrigation reduces mid-century yield shocks by 64% (RCP2.6) or 42% (RCP8.5). When combined with improved maize varieties, irrigation removes the majority of yield shocks (90%) in RCP8.5. We therefore conclude that: (i) irrigation has significant potential to increase resilience in SSA; and (ii) investment in strategies to improve crop varieties is critical if the benefits or irrigation are to be fully realized under an RCP8.5 future.